Erosive Effect of Long-Term Liquid Oral Pediatric Medicines on Permanent Tooth Enamel - Fábio Gomes dos Santos; Ana Maria Barros Chaves Pereira; Isabela Albuquerque Passos Farias; Tibério Andrade dos Passos; Andressa Feitosa Bezerra de Oliveira (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate in vitro the erosive effect of long-term liquid oral pediatric medicines on human enamel teeth and the preventive action of fluoride in an erosive challenge. Material and Methods: Three commonly used medicines were selected for this study, and their endogenous pH was measured in triplicate. Thirty permanent tooth enamel specimens were prepared and divided into six groups (n=5): E1 (Zetalerg), E2 (Betamethasone), E3 (Anemifer), E4 (Anemifer+Duraphat), E5 (Coke), and E6 (artificial saliva). Specimens were immersed in 5 ml of medicine solution for 5 min, 2x/ day for 12 days, and stored in artificial saliva at 37°C between immersions. Data analysis was performed according to the enamel surface morphology using SEM. Results: The medicines showed an acidic pH range from 2.09 to 4.14. All the specimens exposed to pediatric medicines presented some pit-like erosion pattern under SEM analysis, except for the E4 group. The degree of destruction was inversely proportional to pH formulation values. Morphology alterations could be ranked as follows: E3>E2>E1=E5. The E4 group, protected with varnish fluoride, did not present signs of surface erosion wear like E6. Conclusion: All the pediatric medicines used promoted some enamel tooth wear, with higher severity with low pH medicines. The presence of fluoride reduced the deleterious effect of pediatric medicines on human tooth enamel.